1999
DOI: 10.1001/archsurg.134.10.1055
|View full text |Cite
|
Sign up to set email alerts
|

Route of Nutrition Influences Intercellular Adhesion Molecule-1 Expression and Neutrophil Accumulation in Intestine

Abstract: Hypothesis:The levels of intestinal interleukin 10 and interleukin 4, inhibitors of intercellular adhesion molecule-1 (ICAM-1) expression, decline with total parenteral nutrition (TPN). These cytokine changes induced by lack of enteral nutrition may increase ICAM-1 expression, resulting in polymorphonuclear neutrophil accumulation in intestine.Design: Prospective randomized experimental trials. Setting: Laboratory.Materials: Male mice.Interventions: Sixty-three mice were randomized to chow, intravenous TPN, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…In studies of severely injured trauma patients, individuals randomized to enteral feeding sustained significantly fewer pneumonias and intraabdominal abscesses than an injured group fed parenterally [15,[20][21][22]. Experimentally, our work and that of others show that route and type of nutrition influence established mucosal immunologic defenses [13,16], intraperitoneal cytokine and immunologic responses [18], and systemic inflammatory responses to injury [6][7][8]. This work focuses on PN induced alterations in mucosal immunity.…”
Section: Discussionmentioning
confidence: 76%
“…In studies of severely injured trauma patients, individuals randomized to enteral feeding sustained significantly fewer pneumonias and intraabdominal abscesses than an injured group fed parenterally [15,[20][21][22]. Experimentally, our work and that of others show that route and type of nutrition influence established mucosal immunologic defenses [13,16], intraperitoneal cytokine and immunologic responses [18], and systemic inflammatory responses to injury [6][7][8]. This work focuses on PN induced alterations in mucosal immunity.…”
Section: Discussionmentioning
confidence: 76%
“…TPN not only reduces the population of enterocytes but also has been associated with expansion of mucosal goblet cells (GCs) and some lymphocyte subtypes (11,30). Furthermore, newborn (11,19) and adult (17) animal studies indicate that TPN-induced activation of lymphocytes may induce mucosal inflammation on the basis of increased ICAM-1 expression and myeloperoxidase activity. Studies in TPN-fed mice demonstrated that increased expression of the proinflammatory cytokine INF-␥ in activated intraepithelial lymphocytes (IELs) is linked to increased apoptosis and may contribute to the breakdown of epithelial barrier integrity (26,63).…”
mentioning
confidence: 99%
“…18,25 In contrast, in a setting of gut disuse, the same dendritic macrophage samples or ''senses'' bacterial overgrowth of pathogenic bacteria and an absence of food antigen present, and as a result interleukin-12 is released. 25,26 After the sampling of the luminal contents, the dendritic macrophage migrates back down into the lamina propria where there is a bed of naive CD-4 helper T-lymphocytes 18 ( Fig. 3).…”
Section: Why Enteral Nutrition Is Importantmentioning
confidence: 99%
“…29 In contrast, GALT cells which are homing back to the gut to provide protection against luminal bacteria require the expression of mucosal addressin cellular adhesion molecule to pass out of the vascular space and into the lamina propria of the gut. 10,26 With gut disuse and decreases in the T H 2 cytokines, there is down-regulation of mucosal addressin cellular adhesion molecule levels, an effect which essentially closes the door to these GALT cells and prevents their exiting from the vascular space. 10,26 The impact of these physiologic processes is well documented in clinical studies.…”
Section: Why Enteral Nutrition Is Importantmentioning
confidence: 99%
See 1 more Smart Citation